Study of the level of physical ability of 18-20 years old football players during the annual cycle of training - Chernenko, O. Ye.; Hurieieva, A.; Serdyuk, D.; Chernenko, A.; Черненко, Олена Євгенівна (Vancouver : Perfect Publishing, 2022)
The study identified the main stages of training of 18-20 years old players during the annual cycle. It is established that, at the moment, in the system of sports reserve training the task of improving motor skills should remain one of the main throughout the annual cycle, regardless of the stages of training. The purpose of the study is to investigate the dynamics of changes in the physical performance of 18-20 years old football players during the annual training cycle. Methods: analysis and generalization of data from modern sources of information; pedagogical observations; physical fitness testing; pedagogical experiment; methods of mathematical statistics. The research was conducted during the training and participation of football players of IFC "Metallurg-2" (Zaporizhzhya) in the Ukrainian Football Championship among amateur teams 2020/2021. It is established that at the end of the first and second preparatory periods of the 2020/21 season for the majority of 18-20 years old football players, the indicators related to the "average" level of development were recorded. These include - an indicator of physical performance and aerobic capacity of athletes. At the end of the study it was found that all indicators that characterize physical performance, aerobic capacity decreased (p<0.05) and belonged to the functional class "below average" and "average", respectively.
Keywords: physical capacity; football players; annual training cycle; aerobic capacity